THE IMPACT OF SEWAGE WATER ON SOME FISH IN ALKHUMRAH AREA, SOUTH OF JEDDAH GOVERNORATE, SAUDI ARABIA. - Al enzi, omar; Elnaggar, Moustafa; Felemban, Hassan (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
Treated sewage is a source of water and soil pollution despite the development of treatment methods, especially the entry of tertiary treatment into use in most purification plants in the Kingdom. This pollution comes as a result of the high levels of salts of all kinds, especially the remnants of heavy metals that negatively affect the environment and many living organisms. In this field, Alkhumrah station complex in the south is considered one of the largest sewage treatment plants in the Kingdom. It produces large quantities of treated water that are disposed of in seawater, and part of it cuts through the Al-Taawun area in Jeddah, causing pollution of some valleys and negatively affecting some living organisms, including tilapia fish that reproduce naturally in these valleys and lakes. In the context of this situation, this study aimed to know the extent of the impact of treated wastewater on the reproduction and growth of Tilapia Fish. This study showed that this water affected the growth and weight of fish during the months of May to October 2023, February and March 2024, as the weight of the fish ranged from 14.8 to 54.7 gm, while the length of the fish ranged from 84.8 mm during June 2023 to 395.3 mm during March 2024. These changes are attributed to the components of the water during these months, which showed a significant increase in all salts and minerals, including an increase in calcium from 23 mg/L in normal water to 90 mg/L in polluted water, while cadmium increased from 24.6 mg/L to 173 mg/L. As for the fish blood level analyses, the study showed an increase in all the criteria indicating infection and damage to some tissues, including white blood cells (WBC), red blood cells (RBC), platelets (PLT), hemoglobin (Hb), neutrophils (NP), and lymphocytes (LP). This increase coincides with an increase in liver enzymes that indicate liver infections, including alanine aminotransferase (ALT), which increased from 20.36 u/L in normal water to 56.08 u/L in polluted water, also for aspartate aminotransferase (AST) the normal water it was 16.98 u/L and increased in the polluted water during Feb to 35.96 u/L and during Mar to 60.96 u/L. As for the alkaline phosphatase (ALP) enzyme, it also increased from 51.2 to 91.2 u/L. Histological sections documented changes and injuries in the liver, gills, and muscles. Various histological changes have been identified, wherein liver cells exhibited an increase in macrophage aggregation within liver tissues, hepatocyte hypertrophy, and intravascular hemolysis within blood vessels, accompanied by cellular degeneration in the aggregated fish from Alkhumrah area.